2010
DOI: 10.1063/1.3298586
|View full text |Cite
|
Sign up to set email alerts
|

Transition probabilities for the Au (S2, D2, and P2) with SiH4 reaction

Abstract: Transition probabilities on the interaction of the ground and the lowest excited states of gold Au ((2)S:5d(10)6s(1), (2)D:5d(9)6s(2), and (2)P:5d(10)6p(1)) with silane (SiH(4)) are studied through ab initio Hartree-Fock self-consistent field calculations, where the atom's core is represented by relativistic effective core potentials. These calculations are followed by a multiconfigurational self-consistent field study. The correlation energy is accounted for through extensive variational and perturbative seco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2010
2010
2012
2012

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 44 publications
(39 reference statements)
1
2
0
Order By: Relevance
“…In any case, our reported energies are compatible with the spectra of reactants, intermediates, and products. For instance, the probabilities for the Ga + CH 4 reaction agree quite well with experimental results [83,96], whereas those obtained for other systems reported here were widely discussed in the original papers [82][83][84][85][86][87][88]. The potential energy surfaces for the coinage metals Cu and Au with silane are rather similar.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…In any case, our reported energies are compatible with the spectra of reactants, intermediates, and products. For instance, the probabilities for the Ga + CH 4 reaction agree quite well with experimental results [83,96], whereas those obtained for other systems reported here were widely discussed in the original papers [82][83][84][85][86][87][88]. The potential energy surfaces for the coinage metals Cu and Au with silane are rather similar.…”
Section: Discussionsupporting
confidence: 88%
“…Pacheco-Sánchez et al [87] have found that Gold in its second excited state ( 2 P: 5d 10 6p 1 ), through a series Taking it to pass the avoided crossing, it has a probability P = 0.802 [87] for crossing towards C 2 A maintaining the 6p 1 character, where it finds another avoided crossing, and there is a probability of 0.737 for crossing toward B 2 A also maintaining the 6p 1 character. Here it finds another avoided crossing, and there is a probability of 0.803 of crossing toward the A 2 A still maintaining the 6p 1 character (see Figure 4).…”
Section: Interactions Of the Cu Au Coinage Metals With Yhmentioning
confidence: 99%
See 1 more Smart Citation